Aplikasi amalan fiqh sains rumah tangga dan kerjaya dalam kalangan akademis wanita cemerlang - Hamzah, Naemah (2015)
The Tenth Malaysia Plan witnesses an increase in the participation of women as decision-makers in the public sector. Outstanding women of today must therefore apply fiqh practices at home and in their career as a condition of excellence in Islam. This study aims to assess the application of the science of fiqh in practices at home and at work, the characteristics of personality that are classified as excellent, and the factors supporting women academics who excel based on Turath works and the views of contemporary religious scholars. This study is a multiple case study using qualitative design of in-depth interviews and document analysis. A total of seven women academics at public Universities holding grade 54 and the Premier Grade, their spouses, their seven employers, seven children and seven colleagues were selected using the purposive sampling. The five criteria for choosing these female academics are: that they are professional women of the public sector, married, have received at least an award for career excellence, are able to balance their homes and careers, and that they observe the Muslim head-covers. The results were thematically analysed using the NVivo 7.0 software. The study found that Islam allows women to work for as long as the imposing religious limits and conditions are observed. Patterns of the findings also produced the home and career fiqh practices application model involving personality traits and the factors supporting the success of these contemporary women. The formulation of such application model further led to new findings relating to models of excellent spouses, excellent children, excellent parents, excellent co-workers, excellent lecturers, and excellent employers according to Islam. This study model was submitted as a guide to the Ministry of Women and Family Development, the Public Service Department, the private sector, institutions of higher learning, career women, and counsellors in order to generate the quality for the nation's human capital.